2011
DOI: 10.1093/nar/gkr1066
|View full text |Cite|
|
Sign up to set email alerts
|

MeCP2 binds to nucleosome free (linker DNA) regions and to H3K9/H3K27 methylated nucleosomes in the brain

Abstract: Methyl-CpG-binding protein 2 (MeCP2) is a chromatin-binding protein that mediates transcriptional regulation, and is highly abundant in brain. The nature of its binding to reconstituted templates has been well characterized in vitro. However, its interactions with native chromatin are less understood. Here we show that MeCP2 displays a distinct distribution within fractionated chromatin from various tissues and cell types. Artificially induced global changes in DNA methylation by 3-aminobenzamide or 5-aza-2′-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 82 publications
6
71
0
Order By: Relevance
“…3C). This is in agreement with recently published results showing that the majority of MeCP2 from brain and liver is also found in the S1 fraction (37). There were no apparent differences in the distribution of total and phosphorylated MeCP2e1-FLAG between the fractions, as all MeCP2 forms were predominantly found in the active S1 fraction along with the known MeCP2 interacting protein Sin3A (25), while the MeCP2-interacting protein HP1␣ (1) was present in both the S1 and S2 fractions (Fig.…”
Section: Identification Of Mecp2e1 Posttranslational Modifications Bysupporting
confidence: 93%
“…3C). This is in agreement with recently published results showing that the majority of MeCP2 from brain and liver is also found in the S1 fraction (37). There were no apparent differences in the distribution of total and phosphorylated MeCP2e1-FLAG between the fractions, as all MeCP2 forms were predominantly found in the active S1 fraction along with the known MeCP2 interacting protein Sin3A (25), while the MeCP2-interacting protein HP1␣ (1) was present in both the S1 and S2 fractions (Fig.…”
Section: Identification Of Mecp2e1 Posttranslational Modifications Bysupporting
confidence: 93%
“…Finally, in vitro crosslinking experiments suggest that contact occurs between MeCP2 and nucleosomal histone H3 (REF. 68), and it has also been reported that MeCP2 can bind to an isolated N-terminal histone H3 tail 69 . Whether binding to histones represents a mechanism for recruiting MeCP2 to chromatin in vivo has yet to be assessed.…”
Section: Matrix Attachment Regionsmentioning
confidence: 92%
“…In this very coarse fractionation, 71,72 the SI (supernatant) fraction recovered immediately upon nuclease digestion contains digested DNA and nucleosomes from chromatin regions readily accessible to the nuclease (i.e., euchromatic regions). The SI fraction was subsequently fractionated further using a 5-20% sucrose gradient in 25 mM NaCl, 10 mM Tris-HCl (pH 7.5), 0.2 mM EDTA buffer run for 21 h at 96,000 £ g at 4 C. The SE (supernatant) fraction, obtained after hypotonic lysis of the pelleted nuclei, is highly enriched in facultative heterochromatin.…”
Section: Chromatin Fractionationmentioning
confidence: 99%